Pengaruh Kinerja Dan Kualifikasi Akademik Guru Terhadap Mutu Pendidikan - Sitti Nadirah; Ismail Nasar; Arisman Sabir; Arkam Lahiya; Rosa Zulfikhar; Zulharman Zulharman (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the effect of teacher performance and teacher academic qualifications on the quality of education. Education is very important as one of the determinants of the quality of human resources. The type of research used is quantitative research with a design determination and type of research ex post facto. The population in this study were all Darul Iman Private Madrasah Aliyah (MAS) teachers in Palu City. The sample in the study was taken by 20 teachers. Data collection techniques using questionnaires, documentation, and observation. Data analysis techniques using quantitative descriptive analysis techniques and multiple regression. The results of the study found that there was a significant influence between teacher performance on the quality of education at the Darul Iman Private Madrasah Aliyah (MAS) in Palu City, as evidenced by the t value of 3,847 > 2,110 t table. Furthermore, there is a significant influence between the teacher's academic qualifications on the education quality of Darul Iman Private Madrasah Aliyah (MAS) in Palu City, as evidenced by the t-count value of 10,213 > 2,110 t-table. The results of this study indicate that there is a jointly significant relationship between teacher performance and academic qualifications on the education quality of Darul Iman Private Madrasah Aliyah (MAS) Palu City.